Perspektif Hukum Islam terhadap Budaya Mangupa - Nurfitryani Siregar; Linamayasari Siregar; Irmasuryani Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
Mangupa is a traditional ritual that is still preserved by the people of South Tapanuli as a form of gratitude to Allah SWT for success or avoidance of danger. This tradition also aims to return the tondi (soul/spirit) to the body so that a person can return to health. In the Mangupa procession, food is served and